Análise do processo de argumentação e prova em relação ao tópico logaritmos , numa coleção de livros didáticos e numa seqüência de ensino - Silva, Fernando Tavares da (2007)
The objective of this research is to investigate the approach used in proofs and demonstrations of the logarithmic mathematical object, in a collection of textbooks adopted in the Brazilian Secondary School; as well as to conceive and apply a didactic sequence to introduce the student into the deductive mathematical thought. The research intends to answer the following questions: (1) How does the author of the textbooks approach the process of proving, regarding the subject logarithms in his work? Are the readers stimulated to find out proofs in the suggested activities? (2) Which difficulties do first grade students of the Brazilian Secondary School present during a process of proving? In order to answer the first question, we have analysed the collection Matemática for Secondary School by Luiz Roberto Dante, making use of the criteria of the National Book Catalogue for Secondary School (CNLEM). For the second question, we have used some elements of the didactic engineering methodology , making use of the types of proofs by Balacheff. The results of our analysis bring forward that the author of the collection is always concerned about presenting some kind of justification or demonstration for each element introduced. However, there are few activities that stimulate the reader to produce proofs. Regarding the didactic sequence, the research presents some difficulties observed in the process of production of proofs. Furthermore, it shows that the sequence provided the students development from empiric validations to deductive validations